2010
DOI: 10.7205/milmed-d-10-00002
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Comorbidity and Mortality Among Veterans Hospitalized for Congestive Heart Failure

Abstract: A Behavioral Model of Health Services Utilization approach was used to examine the impact of comorbid mental illness on mortality of veterans admitted to Veterans Affairs Medical Centers in fiscal year 2001 with a primary diagnosis of congestive heart failure (n= 15,497). Thirty percent had a psychiatric diagnosis, 4.7% died during the index hospitalization and 11.5% died during the year following discharge. Among those with mental illness, 23.6% had multiple psychiatric disorders. Multivariable logistic regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
1
12
1
Order By: Relevance
“…Not surprisingly, with regard to veterans who survived to very old age, the greatest risk for death was related to hospitalization, nursing home residence, and smoking, which is in line with previous research . Using a nursing home after hospitalization has been one of the most prevalent risk factors for mortality regardless of the aging process . Visiting the ED was protective against death in the oldest group.…”
Section: Discussionsupporting
confidence: 86%
“…Not surprisingly, with regard to veterans who survived to very old age, the greatest risk for death was related to hospitalization, nursing home residence, and smoking, which is in line with previous research . Using a nursing home after hospitalization has been one of the most prevalent risk factors for mortality regardless of the aging process . Visiting the ED was protective against death in the oldest group.…”
Section: Discussionsupporting
confidence: 86%
“…24,25 Moreover, the rate of past-year depression in our sample was 70% higher than that observed among veterans receiving care within a patient-centered medical home. 26 These results highlight the need for mental and physical health integration initiatives to be expanded to include patients with life-limiting physical illnesses.…”
Section: Discussioncontrasting
confidence: 56%
“…[51][52][53][54][55][56][57][58] Rates of alcohol abuse disorder were higher in the present chemically intolerant patients than in their unaffected counterparts, a fi nding that is not necessarily consistent across other samples. Although family histories for alcohol and drug problems are increased in MCS/chemical intolerance, 21 many earlier studies observed increased levels of alcohol intolerance and lower levels of alcohol use in the index cases of chemical intolerance.…”
Section: Key Findingsmentioning
confidence: 85%